Một phương pháp tần số tính ứng ra của hệ tự động tuyến tính không dung bảng H – hàm số - Mạnh, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
In this paper we present a method of determining the time-characteristics of  a automatic control system decribed in complex domain. In results of the method we have obtained a simple formula defining the time-characteristics of any control system acted by arbitrary input signal, which is described in Laplace reflection form. The system can be steady or  non-steady and  can have the time-delay elements in its model.